Efficacy of Sequential Herbicide Applications in Glufosinate- and Glyphosate-Resistant Corn - R. S. Currie; P. W. Geier (Kansas Agricultural Experiment Station Research Reports, 2019)
To determine their efficacy in corn, this study compared two preemergence programs and sequential glufosinate (Interline) or glyphosate (Roundup PowerMax). Control of common sunflower and Russian thistle was excellent regardless of herbicide treatment. Preemergence herbicides alone provided no more than 78% johnsongrass control early in the season. By late season, only those plots receiving Roundup PowerMax had more than 85% johnsongrass control. However, corn yields did not differ among treatments, and all herbicides increased yield 70–97% relative to nontreated corn.
Keywords: repeat applications